Igniting Productivity: How Transformational Leadership and Motivation Shape Productive Work Behavior at PT. Varindo Lombok Inti - Putri Aulia Rahmatin; Abdul Azis Bagis (LP2M IAIN Palopo, 2026)
Productive behavior is a crucial factor in determining organizational effectiveness, particularly in labor-intensive companies that rely heavily on human resources. This study aims to examine the effect of transformational leadership behavior and work motivation on productive behavior among employees of PT Varindo Lombok Inti. Transformational leadership is conceptualized as leadership behavior that inspires, motivates, and encourages employees to exceed performance expectations, while work motivation reflects the internal and external drives that influence employees’ willingness to work productively. Productive behavior refers to employees’ attitudes and actions that contribute positively to work efficiency, quality, and organizational goals.This research employs a quantitative approach using a survey method. The population of the study consists of employees of PT Varindo Lombok Inti, with samples selected using a purposive sampling technique based on predetermined criteria. Data were collected through structured questionnaires measured using a Likert scale. The data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the measurement model and the structural model simultaneously. Prior to hypothesis testing, validity and reliability tests were performed to ensure that the research instruments met the required measurement standards.The results of the study indicate that transformational leadership behavior has a positive and significant effect on productive behavior, suggesting that leaders who demonstrate inspirational motivation, individualized consideration, and intellectual stimulation are able to enhance employees’ productive behavior. In addition, work motivation is found to have a positive and significant effect on productive behavior, indicating that motivated employees tend to show higher levels of responsibility, initiative, and work effectiveness. Simultaneously, transformational leadership behavior and work motivation significantly influence productive behavior. These findings highlight the importance of strengthening leadership practices and employee motivation as strategic efforts to improve productive behavior and organizational performance.